A lei moral e o sentimento do respeito na filosofia prática kantiana - Menotti, Camila Ribeiro (2012)
This dissertation aims to explain and discuss the Kantian proposal regarding the grounds of moral action from the pure practical reason, and the relationship between these grounds and the "moral sense", i.e., the feeling of "respect". Thus, it is presented the reconstruction of the Kantian argumentation concerning the problem of objective validity of the moral law as a determinant of human will, as well as an analysis of the respective sections of the Groundwork of the Metaphysics of Morals and the Critique of Practical Reason, which present the Kant's arguments concerning the relation between the moral law and the feeling of respect, as a central figure to the practice of this law. In order to do so, the first chapter deals with a terminological analysis of the concept of feeling of Respect, distinguishing it from the conception of moral sense and the feeling of happiness. In the second chapter it is intended to show how the moral law can be realized in the hearts of a finite rational human being like a man, in view of the issue of moral motivation and the systematic link between the feeling of respect and the moral law. Finally, in the third chapter, the dissertation addresses the relationship between the feeling of respect and the fact of reason.